Prevalence of Musculoskeletal Disorder in Wrist and Fingers amomg Amateur Piano Players in Vellore - Ashish Mathew A; S.F.Mariyam Farzana (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Now a days the number of students studying piano in tertiary institution is being increasing. The piano player is similar to athletic activity to play the notes accurately. Posture plays a vital role in piano playing. Musicians are prone to injuries due to the nature of musical practice, inappropriate body postures and potentially harmful playing techniques. Majority of amateur players are prone to injuries, the main objective of the study was to find out the prevalence of musculoskeletal discomfort among piano players in three different wrist styles in piano playing. Methodology: A total 150 samples of age 8 to 15 years of both gender from Kingsway music academy. who use to play piano minimum 30 mins with minimum 6 months of learning experience were recruited for the study, initially their level of pain and discomfort in hand and wrist was measured using Cornell hand discomfort questionnaire Conclusion: The statistical analysis shows that there is pain in fourth and fifth finger in all wrist position and also weight playing method has significant pain among three wrist position .This also study concludes that correct positioning during piano playing can minimize the playing related musculoskeletal disorder.